2016
DOI: 10.21649/akemu.v10i1.1141
|View full text |Cite
|
Sign up to set email alerts
|

Association of risk factors of GDM with outcome of GCT in obstetrical population

Abstract: Objective: To determine the association of risk factors of Gestational Diabetes Mellitus (GDM) to outcome of Glucose Challenge Test (GCT). Place and Duration of Study: From February 2000 to October 2000 at the antenatal clinic of Unit-II at Services Hospital. Subject and Methods: One thousand pregnant women attending antenatal clinic at 24-28 weeks of gestation at Services Hospital were included. Glucose challenge test was performed after a history with special reference to diabetic risk factors. Results: Risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Sohail R et al also found similar results to what we noted. 20 Jamshed et al showed GDM in 6.7% women and had significant linkage with increased parity, obesity and family history of DM which is similar to our study. 21 A study conducted in Karachi, Pakistan showed 15.8% women with GDM while study done in Rawalpindi obtained a prevalence rate of 8% which is very close to what we observed.…”
Section: Discussionsupporting
confidence: 92%
“…Sohail R et al also found similar results to what we noted. 20 Jamshed et al showed GDM in 6.7% women and had significant linkage with increased parity, obesity and family history of DM which is similar to our study. 21 A study conducted in Karachi, Pakistan showed 15.8% women with GDM while study done in Rawalpindi obtained a prevalence rate of 8% which is very close to what we observed.…”
Section: Discussionsupporting
confidence: 92%